Use of CLEANED to assess the productive, environmental, and economic impact of dairy farms in the Peruvian Amazon - Oré, Linda; Romero, Gelver; Souza de Abreu, Maria H.; Velarde-Guillén, José; Arango, Jacobo; Ku-Vera, Juan Carlos; Gómez, Carlos (MDPI, 2024)
Dairy farms in developing countries are key to fighting hunger and poverty. However, their environmental and economic impact in the tropical region of Peru has been scarcely studied. The CLEANED tool, developed by the Alliance of Bioversity International and the International Center for Tropical Agriculture, allows us to assess the productive situation and the environmental and economic impact of different dairy systems. The objective of the study was to use the CLEANED tool to evaluate the production, environmental, and economic impacts of extensive and semi-intensive dairy systems in the tropical region of Peru. Data from twelve dairy farms (six extensive and six semi-intensive systems), in two seasons (rainy and dry) were recorded using semi-structured surveys. The required area (ha/year), production (L milk/ha/year), environmental impact (water use in m3/product), and methane (CH4) and nitrous oxide (N2O) emissions in kg CO2eq/kg fat- and protein-corrected milk (FPCM) were estimated, and the economic analysis was performed for each livestock system. Results showed that the required area was of 28.9 and 32.6 ha, milk yield was 382 and 1254 L/ha/year, water use was 0.59 and 0.29 m3/kg FPCM, CH4 emissions were 1.7 and 1.0 kg CO2eq/kg FPCM, and N2O emissions were 0.22 and 0.17 kg CO2eq/kg FPCM, for the extensive and semi-intensive systems, respectively. The study revealed significant positive differences in semi-intensive livestock systems, including increased productivity, the reduced intensity of CH4 and N2O emissions, and greater profitability.